A Thorough Examination Of Deep Learning And Evolutionary Methods In Hyperspectral Image Processing (International Journal of Environmental Sciences, 2025)
Hyperspectral image processing is like a super tool that combines high-tech photography, smart computing, and nature-inspired problem-solving. It helps us gather, understand, and make sense of information from different kinds of light. This special tool is super important in areas like farming, keeping an eye on the environment, and even in defence. Scientists have recently integrated unique problem-solving methods influenced by nature with self-learning deep learning computer algorithms. The way we perceive and utilize hyperspectral pictures has changed significantly as a result of this potent combination. It's similar to providing us with an extremely clear image of items and materials. The key concepts, techniques, and most current advancements in hyperspectral image processing are clearly illustrated in this study. It focuses particularly on the interplay between these evolutionary and deep learning methods. It also emphasizes how this combination can be quite beneficial in a wide range of professions. This serves as a reminder to continue investigating and learning about this fascinating field, which holds great promise for a wide range of scientific and technological fields.